Analisis Komunikasi Antara Orang Tua Dan Anak Dan Pengaruhnya Terhadap Perilaku Anak - Dewi Solehatin; Qoni’ah Nur Wijayani (Institut Nalanda, 2024)
Communication is a reciprocal relationship between humans when there is a similarity in the message conveyed by the communicator and received by the communicant. Relationships between humans will be created through communication, both verbal (language) and non-verbal (symbols, images or other communication media). Communication has two general functions, first, for one's own survival which includes: physical safety, increasing personal awareness. Second, for the survival of society, precisely to improve social relations and develop the existence of a society. (Mulyana, 2002:41-42). One of the environments that has the most influence on a person's social learning process is a family through interpersonal communication. Apart from that, communication is very crucial social interaction occurs, this is because social interaction also requires opponents in interacting. Communication is an important prerequisite for social interaction to occur. Likewise, in the family, the importance of establishing good communication within the family complements each other, including the role of parents towards children. The family is the first environment for children where children receive the first education and love in their lives. Parents play a very important role for children, where parents must supervise the process of forming children's behavior patterns, supervise, guide, provide knowledge, provide direction and establish good interactions. This research uses a pragmatic/interactional view of communication theory, descriptive research methods.